The first equation can be further simplified so first do that by subtracting 15 to both sides
y - 3x + (15 - 15) = 10 - 15
y - 3x = -5
We know from the second equation that y is 6 - 4x so in the equation y - 3x = -5 plug in 6 - 4x for y
(6 - 4x) - 3x = -5
6 - 4x - 3x = -5
Combine like terms
6 - 7x = -5
(6 - 6) - 7x = -5 - 6
-7x = -11
Isolate x
-7x/-7 = -11/-7
x = 11/7
To solve for y plug in 11/7 in for x in the equation 6 - 4x = y
6 - 4(11/7) =y
6 - 44/7 = y
y = -2/7
so...
(11/7 , -2/7)
Hope this helped!
~Just a girl in love with Shawn Mendes